The Teaching of General College Physics in Jolo - Helen Abbas Cabajon (Community Medicine and Education Journal, 2022)
The purpose of this study is to record, examine and describe the common teaching strategies employed by college faculty members teaching general college physics in the five colleges in Jolo and to know as well what combination of teaching strategy employed by physics teacher in Jolo enhances achievement scores of students. Likewise, the evaluation on the learning facilities used in teaching physics was also taken into consideration. The study utilized the descriptive method of research and the normative survey technique was used for data gathering Purposive sampling was utilized and the respondents taken were composed of all faculty members handling college physics subjects and their respective students enrolled during the second semester of school year 2010 to 2011. The findings showed that the top three most common teaching strategies employed by teachers in teaching general college physics in Jolo are: problem solving, lecture, and board work. These strategies enhanced achievement scores of students. On the other hand, as far as learning facilities are concerned they were inadequate as most important equipment and tools necessary in the teaching of physics subjects were not available and if existing they were not functioning. However, despite the inadequacy of learning facilities, majority of the students have higher probability of passing the course based on their midterm exam. It is highly recommended that physics teachers must be exposed to various teaching strategies in order for them to be abreast with the latest methods in teaching physics. Furthermore, administrators are urged to upgrade school laboratories by procuring equipment, materials and other learning facilities indispensably needed in the teaching of general college physics.